Genetic admixture, inbreeding and heritability estimates in captive African cheetahs (Acinonyx jubatus) including linkage analysis for the King cheetah phenotype - Guthrie, Alan John (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2011.